FAMILY KNOWLEDGE ON PREHOSPITAL STROKE DETECTION CORRELATES WITH HOSPITAL ARRIVAL TIME IN STROKE PATIENTS AT THE NAVAL HOSPITAL DR. RAMELAN, SURABAYA - Ainiyah, Nur; Izzah, Shobibatur Rohmah; Zahroh, Chilyatiz; Bistara, Difran Nobel; Faizah, Imamatul (Universitas Nahdlatul Ulama Surabaya, 2021)
Background: Successful stroke management depends on the speed, accuracy, and timeliness of the initial treatment. Stroke patients with immediate medical help can minimize permanent disability and even mortality. Objective: This study analyzes the correlation between family knowledge on prehospital stroke detection with hospital arrival time. Method: The research design was correlational analytic with a cross-sectional approach. This paper was conducted at the Naval Hospital Dr.Ramelan, Surabaya, from January to February 2019, with ethical clearance from the hospital. The independent variable was family knowledge on prehospital stroke detection, and the dependent variable was hospital arrival time. There were 115 population and 111 samples by consecutive sampling technique. The instrument to measure family knowledge was a questionnaire about prehospital stroke detection consisted of 30 items, while to evaluate hospital arrival time was data from the medical record. The data analysis used the Mann-Whitney statistical test with a significance of 0.05. Result: Most respondents had adequate knowledge regarding prehospital stroke detection (54.1%) and early hospital arrival time (59.5%). There was a correlation between family knowledge on prehospital stroke detection and hospital arrival time in stroke patients (p=0.000). Conclusion: The better family knowledge on prehospital stroke detection, the faster hospital time arrival. Health workers should give health education on prehospital stroke detection to prevent delayed hospital arrival. Further research could involve electronic and social media to improve knowledge on prehospital stroke detection.